Fame and factions: A process-tracing analysis of the 2019 leadership selection process in the Belgian French-speaking liberal party (MR) - Legein, Thomas; van Haute, Emilie (Frontiers in Political Science, 2022)
This study applies process-tracing methods to understand the 2019 leadership selection process in the Belgian French-speaking liberal party, MR, which is the oldest and second largest party in French-speaking Belgium. We triangulate a variety of sources to assemble a rich qualitative material that is used to contrast the formal rules and outcome of the race to the actual process. We show that the gatekeepers were not the ones ascribed in the statutes, that formal rules were bent to fit the profile of the race, and that the very nature of the race was much closer to a coronation than the results may suggest. We also uncover mechanisms through which party actors, especially the incumbent leader as steering agent, informally influence the process to the desired outcome, with the race being played prior to the validation of the candidacies. This analysis puts focuses on when and how key actors use their informal influence to weigh the process and influence the outcome of leadership races.